2006
DOI: 10.2298/hel0645089v
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of wild sunflower by seed and persistant basal stalks in some areas of Central Italy

Abstract: In some sites of Central Italy wild sunflowers are spreading from marginal areas into cropped fields. Crops like maize, tomato, tobacco, alfalfa are often infested with wild sunflowers. Hybrid sunflower crops are also infested with wild material. Plants and populations of wild sunflower also spontaneously grow at the edge of the fields, and along the ditches and roads. We have observed that wild sunflower is partially dispersed by its seed, but possibly it can propagate vegetatively by its perennial basal stal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
(3 reference statements)
0
13
0
1
Order By: Relevance
“…This hypothesis has already been mentioned for Spain and Italy (Vischi et al 2006). This origin has been demonstrated for other species, for instance weed beets (Boudry et al 1993).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This hypothesis has already been mentioned for Spain and Italy (Vischi et al 2006). This origin has been demonstrated for other species, for instance weed beets (Boudry et al 1993).…”
Section: Discussionmentioning
confidence: 56%
“…Fig. 1), have been described for decades in Italy (Vischi et al 2006), Spain (Faure et al 2002) and Central Europe (Holec et al 2005). They were officially confirmed in France in 2004 (Muller et al 2006) although some farmers have been confronted with them since as early as 1990.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Wild, weedy and feral sunflower populations are of concern in several regions of the world because of their invasive capacity and crop interference (Bervillé et al 2005;Vischi et al 2006;Müller et al 2006;Stanković-Kalezić et al 2007). The invasive capacity of H. petiolaris is unknown, since Argentina is the only reported case of this species' invasion in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the present study is the first attempt to elucidate the status and intraspecific relationships in Pterocarya genus from the Hyrcanian and Zagrossian forests of Iran. Although the trnH-psbA spacer has been discussed as a potential barcoding region (Kress et al 2005;Vischi et al 2006;Kress & Erickson 2007), it did not show any polymorphisms in the genus Pterocarya. However, we have found that the two main populations of P. fraxinifolia species (Iranians and from GeneBank) differed in their secondary structure and repeat sequences of ITS2 region, which was recently suggested to be a DNA barcode.…”
Section: Resultsmentioning
confidence: 86%